2018
DOI: 10.1097/jsa.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Osteotomies in Patello-Femoral Instabilities

Abstract: Patellar instability is defined by clinical and radiologic criteria. The surgical treatment is aimed at restoring the congruence of the patellofemoral articulation and correcting extensor mechanism malalignment, to prevent recurrence of dislocation. The standard soft-tissue procedures are lateral release and vastus medialis advancement and medial patello femoral ligament plasty. Bony procedures are frequently performed in addition to soft-tissue surgery, to realign the extensor mechanism by means of tibial tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 15 publications
2
126
0
4
Order By: Relevance
“…[29,30] Second, we found that similar morphologic anomalies of the trochlear aspect, as encoded by similar HP parameters, are actually attributed to different severity grades in the Dejour classification. [14] This finding is in agreement with recent works in the literature reporting that morphometric parameters can optimistically discriminate between the Grade A and the three remaining grades. [15,16] Equivalently, the Dejour classification was shown to be meaningfully effective in separating low-grade from high-grade cases.…”
Section: Main Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…[29,30] Second, we found that similar morphologic anomalies of the trochlear aspect, as encoded by similar HP parameters, are actually attributed to different severity grades in the Dejour classification. [14] This finding is in agreement with recent works in the literature reporting that morphometric parameters can optimistically discriminate between the Grade A and the three remaining grades. [15,16] Equivalently, the Dejour classification was shown to be meaningfully effective in separating low-grade from high-grade cases.…”
Section: Main Findingssupporting
confidence: 83%
“…[11][12][13] One of the most applied clinical approach to score the morphologic anomalies of the trochlear surface (TS) is based on the Dejour classification, which encompasses four different qualitative Grades (A, B, C, D) of increasing severity. [14,15] Based on radiological assessment, the evaluation is performed by means of clinical signs, such as the shape of the groove, the roundness of the two facets and their absolute and relative sizes. Specifically, the four grades encode the 'shallow trochlear groove', 'flat trochlea', 'medial hypoplasia with potential lateral convexity', and 'excessive asymmetry of the trochlear facets', respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6,38 We would therefore agree with the their conclusions, along with those of Fulkerson et al and Dejour et al, who have implied Merchant projections may be preferred over sunrise projections for evaluating trochlear depth. 1,25,34,37,39 To our knowledge, this experiment provides the first objective validation of such. However, on the basis of these data, we would also challenge providers to consider altering the beam orientation angle in this view by 20 degrees (from 60 to 40 degrees caudally) if they are intending to evaluate trochlear depth radiographically.…”
Section: Discussionmentioning
confidence: 81%
“…In the first classification of Dejour, TD was divided into three types. After improvements, a more precise four‐type classification of TD was proposed. In addition, three different patellar types were described by Wiberg; a fourth type (the “Jaegerhut” patella) was later described by Baumgartl.…”
Section: Discussionmentioning
confidence: 99%